Odpowiedzi

2010-04-13T21:46:46+02:00
A) 3x-15>2x
3x-2x > 15
x > 15

b) 5 < x + 3,5
-x < 3,5 - 5
-x < - 2,5 /:(-1)
x> 2,5

f) 0,5x + 1 > 2(3 - x)
0,5x + 1 > 6 - 2x
0,5x + 2x > 6 - 1
2,5x > 5/:2,5
x > 2
2010-04-13T21:48:05+02:00
Rozwiąż nierówność
a) 3x - 15 > 2x
3x-2x>15
x>15
b)5 < x + 3,5
-x<3,5-5
-x<-1,5 /:(-1)
x>1,5
c)-5(1-x) ≥ 5
-5+x≥5
x≥10
d) (x - 2) - 4(3 - x) ≥ 6
x-2-12+4x≥6
x+4x≥6+12+2
5x≥20 /:5
x≥4
e) x + 4/2 - 6 ≥ 0
x≥6-2
x≥4
f) o,5x + 1 > 2(3 - x)
0,5x+1>6-2x
0,5x+2x>6-1
2,5x>5 /:2,5
x>2
2010-04-13T22:06:10+02:00
A)3x - 15 > 2x
3x - 2x > 15
17 > 15 / : 1
x > 15

b)5 < x + 3,5
x < 3,5 - 5
x > -1,5

c)-5 (1 - x ) ≥ 5
-5 + 5x ≥ 5
5x ≥ 5 +5 / : 5
x ≥ 2

d)(x - 2) - 4(3 - x) ≥ 6
x - 2 - 15 + 4x ≥6
x + 4x ≥ 6 + 2 + 15
5x ≥ 23 / : 5
x ≤ 4,6

e)x + 4/2 - 6 ≥ 0 / *2
2x + 4 - 12 ≥ 2
2x ≥ 12 - 4
2x ≥ 16 / : 2
x ≤ 8

f)0,5x + 1 > 2(3-x)
0,5x + 1 > 6 - 2x
2x + 0,5x > 6 - 1
2,5x > 5 / : 2,5
x > 0,5